Effects of Exposure to Ultrasonic Waves on Extraction of Evaporation Methods on The Anthocyanin Content of Green Betal and Basil Leaves - Mokhamad Tirono (Postgraduate, University of Mataram, 2022)
Synthetic anticancer agents have serious side effects on health. Therefore, it is necessary to develop natural anticancer agents with better effectiveness for cancer treatment. This study aims to determine the effect of exposure to ultrasonic waves on the extraction process by evaporation method on grain temperature, yield, and anthocyanin content of green betel and basil leaf. Exposure was carried out using 120 W ultrasonic waves for 0-30 minutes. The results showed that exposure for 30 minutes increased the temperature of the green betel leaf and basil leaves from 27oC to 52oC. Extraction by exposure to ultrasonic waves for 10 minutes obtained the highest yields of 13.87±1.10 % and 18.73±3.74% for green betel and basil leaf, respectively. Extraction with ultrasonic wave exposure time of 25 minutes resulted in the highest anthocyanin content, namely 490.10±6.67 mg/L and 242.65±9.09 mg/L for green betel and basil leaf, respectively. The high anthocyanin content is influenced by the exposure time and the temperature of the extracted granules. The time of exposure to ultrasonic waves of more than 25 minutes makes the grain temperature more than 50oC, so that the anthocyanin content of the extraction results decreases